Family Health Promotion Through Dietary Management for Diabetes, Hypertension, and Household Waste Management: Promosi Kesehatan Keluarga Melalui Pengelolaan Makanan Kelompok DM, Hipertensi, dan Pengelolaan Sampah Rumah Tangga - Nurlailis Saadah; Budi Yulianto; Rahayu Sumaningsih; Uswatun Khasanah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The number of DM (Diabetes Mellitus) and hypertension sufferers in Tambakrejo is increasing year by year. This requires breakthrough measures for prevention and treatment. This community service activity aims to improve the knowledge and skills of food management in DM and hypertension client groups, as well as knowledge and understanding of disease prevention caused by unhealthy environments. The habit of Clean and Healthy Living (PHBS) can begin with independent household waste management. This activity was implemented by health cadres and elderly cadres, under the guidance of community service workers and students. The method used was a combination of community development models, participatory rural appraisal (PRA) models, and participatory technology development. After the implementation of the activity, there was a 20% decrease in the number of hypertension sufferers and a 15% decrease in DM sufferers. Monitoring, evaluation, and follow-up were carried out by the village head, village midwife, nurse from the Tambakrejo village health post, and the head of the Candirejo Community Health Center.